The Poetics of Translation According to Javier Marías: Theory and Practice - Pegenaute, Luis (TTR, 2012)
This article studies the activity undertaken by Javier Marías involving translation. The presence of translator protagonists in his novels is studied, together with his theoretical position on translation and his facet as a translator himself. In all three fields the following of a fully coherent poetics in his aesthetic convictions regarding translation is observed, for Marías rejects traditional stances that make of translation a secondary activity when compared with original composition, thus identifying writing with re-writing without any type of hierarchical prejudice.